IMPACT OF THE DOUBLING FARMERS’ INCOME (DFI) PROGRAMME ONKNOWLEDGE, ADOPTION, PRODUCTIVITY AND INCOME OF GROUNDNUTGROWERS IN NAGARKURNOOL DISTRICT OF TELANGANA - B. RAJASHEKAR, M. JAGAN MOHAN REDDY, T. PRABHAKAR REDDY, O. SHAILA and M. RAJASHEKHAR (The Journal of Research, PJTSAU, 2026)
Groundnut is one of the major oilseed crops of southern Telangana and contributes substantially to the livelihood of smalland marginal farmers, with Nagarkurnool district alone accounting for just over half of the State entire groundnut growing area.Despite the availability of improved production technologies, adoption has remained suboptimal because of limited technicalknowledge, inadequate extension support and resource constraints. To address these gaps, Krishi Vigyan Kendra (KVK), Palemimplemented the Doubling Farmers’ Income (DFI) Programme, promoting scientific groundnut production technologies throughdemonstrations, farmer training, exposure visits and regular technical advisories. The present study assessed the programme’simpact on knowledge, adoption, productivity and income of beneficiary farmers. An ex-post facto research design was employedwith 240 beneficiary farmers selected from Nandivaddeman village (Bijinapally Mandal) and Gummakonda village (ThimmajipetMandal), 120 respondents from each. Overall mean knowledge and adoption of nineteen recommended best managementpractices rose from 35.11% and 32.10% before the programme to 89.26% and 84.25% after it. Pod yield increased by 26.6%(2,180 to 2,760 kg ha-1), net income by 51.3% (Rs. 74,200 to Rs. 1,12,300 ha-1) and the Benefit–Cost ratio from 1.46 to 2.01; pairedt-tests confirmed that gains in knowledge, adoption, yield and income were all highly significant (p < 0.01), with Cohen’s dexceeding 1.0 throughout, indicating large effect sizes. Chi-square tests of association further confirmed that the before-afterincrease in adoption was statistically significant for every one of the nineteen practices individually (p < 0.001), with Cohen’s hconsistently above 1.0, the largest effects recorded for practices seed treatment, soil testing, Integrated Pest Management thathad the lowest pre-programme adoption base. The study demonstrates that integrated demonstration-led extension interventionsunder DFI significantly improved groundnut productivity and profitability among resource-poor farm households in Nagarkurnooldistrict. Beneficiaries showed predominantly medium risk orientation but high innovativeness and achievement motivation, abehavioural profile consistent with the breadth of adoption observed; the high cost of fertilizers and plant-protection chemicals,labour scarcity, erratic rainfall, disease incidence and delayed seed availability were the constraints most frequently cited byfarmers, closely mirrored by their own suggestions for subsidized inputs, stronger price support, continued training and expandedcustom-hiring access.